HYPNOTHERAPY RELIEVES PAIN IN THE 1ST STAGE OF LABOR AT BANDUNG PRIVATE HOSPITAL - Susilowati, Yuanita Ani; Martini, Flora Maria; Suntoro, Henri; Wijaya, Yosi Maria; Hardjanti, Therese Maura; Sihombing, Ferdinan (Jambura Nursing Journal, 2025)
The pain experienced during the first stage of labor varies for each individual, depending on the pain threshold of each patient. Despite the implementation of Cognitive Behavior Therapy (CBT) and relaxation techniques in pain management at Bandung Private Hospital, some patients still endure persistent pain. The use of hypnotherapy as a non-pharmacological approach to alleviate pain has not been widely adopted. This study aims to evaluate the impact of hypnotherapy on the level of pain during the first stage of labor. Employing a Quasi-experimental design with a single-group pre-test and post-test without control, the researcher administered hypnotherapy techniques for 15-30 minutes. Pain levels were assessed using the Numeric Rating Scale among 14 parturient women. Comparing the pre-test and post-test measurements of pain levels, the results demonstrated a significant reduction in the first stage labor pain due to hypnotherapy (p < 0.05). Before the intervention, the mean pain level was 3.29, which decreased to 2.64 after hypnotherapy. This study's findings indicate that hypnotherapy is effective in reducing pain during the first stage of labor. The implications of these findings are crucial in enhancing the quality of care for laboring mothers. It is hoped that hypnotherapy can be widely applied in the management of labor pain in various hospitals, taking into account appropriate implementation processes and individual patient needs.